No tillage farming of black beans in wheat stubble for self propelled harvesting - Alonço, Airton dos Santos; Antunes, Irajá Ferreira (Pesquisa Agropecuaria Brasileira, 1997)
The influence of wheat stubble shadding on the height of insertion of black beans (Phaseolus vulgaris L.) pods for self propelled harvesting was evaluated in this study. The effects of five wheat stubble heights (0.00 m, 0.10 m, 0.20 m, 0.30 m and 0.40 m) were studied. The black beans cultivars, BR-IPAGRO 2 - Pampa and BR-FEPAGRO 44 - Guapo Brilhante, were sowed through no tillage farming. The treatments were arranged in a split plot design with different treatments levels randomized within each complete block, with three replications. The insertion height of pods was determined by two variable: measuring the distance from the lower pod tip to the soil surface, and from its peduncle insertion to the soil surface. Analysis of variance showed statistical significant differences between treatments in the two variables, but not in grain production. These results confirm the hypothesis that the wheat stubble shadding induces the black beans plant to set pods at a height compatible with the height required for the self propeled harvesting, reducing harvesting losses, without impairing crop productivity.
Keywords: Phaseolus vulgaris; wheat straw; agricultural mechanization; shadding